IMP1 3′ UTR shortening enhances metastatic burden in colorectal cancer. (8th November 2018) - Andres, Sarah F; Williams, Kathy N; Plesset, Jacqueline B; Headd, Jeffrey J; Mizuno, Rei; Chatterji, Priya; Lento, Ashley A; Klein-Szanto, Andres J; Mick, Rosemarie; Hamilton, Kathryn E; Rustgi, Anil K
Abstract: The RNA-binding protein insulin-like growth factor 2 mRNA binding protein 1 (IMP1) is overexpressed in colorectal cancer (CRC); however, evidence for a direct role for IMP1 in CRC metastasis is lacking. IMP1 is regulated by let-7 microRNA, which binds in the 3′ untranslated region (UTR) of the transcript. The availability of binding sites is in part controlled by alternative polyadenylation, which determines 3′ UTR length. Expression of the short 3′ UTR transcript (lacking all microRNA sites) results in higher protein levels and is correlated with increased proliferation. We used in vitro and in vivo model systems to test the hypothesis that the short 3′ UTR isoform of IMP1 promotes CRC metastasis. Herein we demonstrate that 3′ UTR shortening increases IMP1 protein expression and that this in turn enhances the metastatic burden to the liver, whereas expression of the long isoform (full length 3′ UTR) does not. Increased tumor burden results from elevated tumor surface area driven by cell proliferation and cell survival mechanisms. These processes are independent of classical apoptosis pathways. Moreover, we demonstrate the shifts toward the short isoform are associated with metastasis in patient populations where IMP1 -long expression predominates. Overall, our work demonstrates that different IMP1 expression levels result in different functional outcomes in CRC metastasis and that targeting IMP1 may reduce tumor progression in some patients. Abstract : Our work demonstrates that in colon cancer, shortening of the 3′ untranslated region of the RNA-binding protein IMP1 enhances IMP1 protein expression, tumor size and metastatic burden to the liver. Elevated proliferation and cell survival promote tumor growth.